Economic Freedom, Human Rights, and the Returns to Human Capital : An Evaluation of the Schultz Hypothesis - King, Elizabeth M. (2012)
According to T.W. Schultz, the returns to human capital are highest in economic environments experiencing unexpected price, productivity, and technology shocks that create "disequilibria." In such environments, the ability of firms and individuals to adapt their resource allocations to shocks becomes most valuable. In the case of negative shocks, government policies that mitigate the impact of the shock will also limit the returns to the skills of managing risk or adapting resources to changing market forces. In the case of positive shocks, government policies may restrict access to credit, labor, or financial markets in ways that limit reallocation of resources toward newly emerging profitable sectors. This paper tests the hypothesis that the returns to skills are highest in countries that allow individuals to respond to shocks. Using estimated returns to schooling and work experience from 122 household surveys in 86 developing countries, this paper demonstrates a strong positive correlation between the returns to human capital and economic freedom, an effect that is observed throughout the wage distribution. Economic freedom benefits those workers who have attained the most schooling as well as those who have accumulated the most work experience.